2002
DOI: 10.1021/jp0144000
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Electrostatic Interaction of Ions in Dry, Isolated Micelles of AOT by the Method of Direct Optimization

Abstract: A simple model of a dry reversed micelle of ionic surfactants is proposed, according to which during the optimization procedures the ions move over certain closed surfaces in a vacuum at T = 0 K .The electrostatic interactions of discrete ions in dry, reversed micelles of AOT are calculated as a function of the sizes of the ions, ion charges, and the optimum positions of the ions in the polar cavity of the micelles. It is shown that when the counterions penetrate the layer of the potential-determining ions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…We therefore concluded that [Na n+z AOT n ] z+ self-assembles into a multiply charged reverse micelle in the gas phase, with an inner core composed of hydrophilic polar head groups and counterions, and hydrophobic alkyl tails protruding into the vacuum. Parallel to experimental advances, molecular dynamics (MD) simulations have demonstrated that NaAOT reverse micelle remains stable in vacuo [17][18][19], with apolar tails collapsing on the outer surface to make the structure more compact [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore concluded that [Na n+z AOT n ] z+ self-assembles into a multiply charged reverse micelle in the gas phase, with an inner core composed of hydrophilic polar head groups and counterions, and hydrophobic alkyl tails protruding into the vacuum. Parallel to experimental advances, molecular dynamics (MD) simulations have demonstrated that NaAOT reverse micelle remains stable in vacuo [17][18][19], with apolar tails collapsing on the outer surface to make the structure more compact [17].…”
mentioning
confidence: 99%
“…z+ be destabilized because of Coulombic repulsion when Na + ions are too close to each other? Based on a direct optimization of dry, isolated NaAOT reverse micelles [17] and MD simulations of low water content NaAOT reverse micelles in isooctane [49,50], most Na + ions penetrate the layer of AOT polar heads and coordinate with the sulfonate group. Some Na + ions exist outside and coordinate with the carbonyl group.…”
mentioning
confidence: 99%
“…On the other hand, it was reported that the anionic surfactant NaAOT can be made to form micelles with diverse shapes by adjusting experimental parameters. [33][34][35][36] The self-assembled AOT À layers at the interface of water and oil could act as template for growing ZnO Fast growth along h21 1 0i results in the formation of a hexagonal disk (Figure 5 a). Slight bending of the selfassembled AOT À monolayer makes it possible to accommodate local strain in the disk by formation of small-angle grain boundaries closely parallel to {21 1 0}.…”
mentioning
confidence: 99%
“…A value of 0.63 nm 2 was taken for the area per one molecule of AOT in the surface layer [16]. Our calculations show that, e.g., the numerical concentra tion of empty micelles at a concentration of silver in solution of 1.25 mmol/L and with hydrodynamic radii of 2.4 and 10.2 nm for empty micelles and micelles with nanoparticles, respectively, was N m = 3.9 × 10 21 L ⎯1 , while the concentration of micelles with nanoparticles was N Ag = 4.7 × 10 15 L -1 .…”
Section: C N Rmentioning
confidence: 99%